The role of the student management assistant as an accompaniment for students with special education needs with visual impairment in the inclusive education program for sciences subject - Nordin, Mohd Norazmi; Abd Wahab, Maryati; Hashim, Siti Noor Aneeis; Ismail, Albert Feisal @ Muhd Feisal; Abbas, Mohd Saleh; Abd Ghani, Amirul Haqeem; Maidin, Siti Sarah (African Science Publications, 2024)
In Malaysia, PPM are not university graduates and have minimal theoretical knowledge about early childhood (Janon, N. S., & Abdul Khaiyom, J. H, 2020). According to the Education Services Commission (SPP), (2020) Student Management Assistant (PPM) is a service scheme in the administrative and support group of the Education Services Commission (SPP), where this appointment scheme has a minimum appointment qualification in the Malaysian Certificate of Education (SPM). This appointment placement is under the Malaysian Ministry of Education (KPM) and is permanent. The PPM position is divided into a number of job functions, namely pre-school management, dormitory management, and integration special education program management.